Association between Vitamin D Receptor methylation with vitamin D, parathyroid hormone levels and lipid profile in normal and obese Saudi Females - AlSedairy, Sahar Abdulaziz; Binobead, Manal Abdulaziz; Al-Harbi, Laila Naif; Syed, Naveed Ahmad; Subbarayan, Periasamy Vaiyapuri; Arzoo, Shaista; Alshatwi, Ali Abdullah (Progress in Nutrition, 2021)
Obesity has been encountered as one of the most common disorder with major public health implications. Various epidemiologic, genetic and metabolic data have shown significant role of vitamin D in obesity. The purpose of this study was to determine the connotation between VDR methylation at three sites and various variables such as weight, height, BMI, waist circumference, lipids profile (TG, HDL-C, LDL-C and total cholesterol), vitamin D, and PTH in normal and obese Saudi females. For this purpose; 100 Saudi females (31 normal weight with BMI<25 and 69 obese with BMI>30) with no chronic diagnosed diseases aged from 18 to 60 years were evaluated. Spearman rank correlation coefficient (R) with graphic representations using linear regression has been used to find the correlation between various variables. In studying the VDR methylation correlations with different variables, the results showed that; methylation of VDR at site 1 showed positive non-significant correlation with weight, BMI, serum TG and LDL levels in addition to serum vitamin D level. On the other hand, there was negative correlation with TC, HDL and PTH (parathyroid hormone). These results indicated that; methylation at site 1 could decrease PTH, HDL & TC levels. Furthermore, methylation of VDR at both site 2 and site 3 showed positive non-significant correlations with TC, TG, LDL levels in addition to serum levels of vitamin D and PTH. While it showed a negative correlation with only HDL level. Methylation of VDR at site 2 and 3 is related with obesity, it was significantly correlated with weight, BMI and waist circumference.